ANALISIS SISTEM KENDALI DUA POSISI PADA SOLENOID VALVE UNTUK PRODUK BIOGAS CONTROL AND MONITORING (COMMON-BIGOT) FROM ANIMAL WASTE - Imam Arifin (Politeknik Negeri Ketapang, 2021)
Biogas is gas produced by bacteria when organic matter undergoes a fermentation process under anaerobic conditions, and will produce methane gas which is temporarily stored in a container called a biogas bag. The biogas bag needs to be controlled to ensure the biogas bag remains safe. The control system is in the form of a two-position control because it has the advantage of being cheap and simple, besides that the solenoid valve as an actuator has a non-linear output property. To detect the capacity of the biogas bag, the HCSR-04 proximity sensor is used as feedback on the set point value that is set, which is 50 cm for the maximum set point and 30 cm for the minimum set point. The results obtained by the proximity sensor is able to read the distance with an accuracy of 5.8% and the On-Off control has a response of 0.25 seconds.